Presidential decree No. 341/2017 on establishing the economic zone of the golden triangle & Prime minister decree No. 1788/2017 on the establishment of the public authority for the economic zone of the golden triangle / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 47/2017